What are the criteria for selecting people to whom the services of microfinance should be provided in order to maximize the impact on poverty alleviation? - Farooq, Sharjeel (2011)
1.7 billion people are estimated as victim of absolute poverty in today’s world. Tremendous efforts are going on by organizations throughout the world but still the number of human beings living under 2 dollars of income per day is not reducing rapidly. Microfinance serves a category that lies above the absolute poor called ‘relative poor’. These are the people who have potential to survive on their own and to sustain the hardships of this fast pace world. This study is aimed to focus on the selection criteria of the potential clients of microfinance services. A review of existing literature revealed that there is strong debate about sustainability of microfinance institutes (MFIs) and reaching the ‘poorest of the poor’. Besides this argument the study revolves around the three main issues that are directly affiliated with the client selection of microfinance. In-depth analysis is made for the issues like inclusiveness of non-poor in facilitating microfinance services; gender preference for provision of microfinance services depending on the geographic location of availability of MFIs programs; declaration of overall positive impact of microfinance on society and extending the service of microfinance to the dwellers of developed countries. The findings are based on existing literature as well as on the primary research conducted by the author. The primary research contributes by getting valuable insights from a structured questionnaire that has enabled the author to come up with detailed analysis and recommendations.